The other pandemic in Peru: corruption and its impact on democracy - Buleje Buleje, Pedro Rómulo (2023)
Corruption weakens the institutionality, and with this, not only social disorder is favored and public trust is eroded, but it also limits national development, hence its effects undermine the pillars of democracy. In this century, Peru has been the scene of various cases of corruption that have involved national elites from different social strata such as politics, business, justice, military and police. From a systemic perspective, the impact of corruption on the democratic political system can be modeled from an iterative process of certain interrelated key components inherent to democracy, such as: institutionality, governability, and public policies understood as mechanisms available to governments to achieve national development whose objectives are set in the Strategic Plan for National Development to 2050. The assessment of these key components, through internationally validated qualitative instruments, allows us to corroborate that corruption in Peru continues to be the main factor that has generated the decline of these components, seriously hindering national development and thereby fostering a systemic crisis and the questioning of democracy.